The neglected need for psychological intervention in patients suffering from incidentally discovered intracranial aneurysms - Wenz, Holger; Maros, Máté E.; Groden, Christoph (Clinical neurology and neurosurgery, 2016)
Objectives - Previous studies demonstrated a conspicuously elevated rate of psychiatric disorders in patients with incidental intracranial aneurysms. This study was designed to analyze the impact of this observation on the post-interventional rates of PTSD, depressions and anxiety disorders in this collective. - Methods - Physically unaffected iA patients with an unremarkable medical history were included in this two center study. Pre-interventional psychiatric histories, rates of post-interventional depressions, subjective trauma, PTSD, and pre-interventional fears were determined by questionnaires (Beck Depression Inventory (BDI), Impact of Event Scale (IES), civilian Post-traumatic-Stress-Disorder (PTSD) Check List (PCL-C)). Benign meningioma (M) patients served as controls. - Results - 58M and 45 iA patients were enrolled. Significantly higher rates of PTSD, elevated trauma scores, and moderate/severe depressions (PTSD: p=0.0017; IES: p=0.0038; BDI: p=0.0301) were demonstrated in the iA collective. After excluding patients with a positive pre-interventional psychiatric history those differences were not reproducible. 70% of the iA patients reported an improvement of their unspecific pre-interventional symptoms, while 30% would have rated a psychological consultation as helpful. - Conclusion - The data identifies the early psychological consultation as a relevant and by affected patients accepted treatment modification when trying to improve the outcome after treatment of incidental aneurysms.
Gesehen am 23.04.2019